Повышение стойкости режущего инструмента из быстрорежущей стали для обработки глубоких отверстий путем заточки и доводки алмазным инструментом - Маршуба, Вячеслав Павлович; Дрожжин, В. И. (НТУ "ХПИ", 2003)
In this article are considered the results of investigation: how the surface smoothness, obtaining after grinding and smoothing by synthetic diamond abrasive tool, influence on cutting tool life, if this cutting tool have been made of quick-cutting steel. The obtained results allowed ascertaining the dependence of cutting tool life on surface smoothness.
Keywords: обработка механическая; резание; инструмент абразивный; заточка чистовая; круг шлифовальный